Influence of Growth Conditions on Production of Klebicin K and Raoultellin L, Two Antimicrobial Substances against Gram-Negative Pathogens - Nascimento, S (International Journal of Pharmaceutical & Biological Archive, 2011)
ABSTRACTKlebicin K and raoultellin L are two bacteriocins produced by Klebsiella ozaenae K and Raoultella terrigena L, respectively. They possess antimicrobial activity against foodborne pathogens belonging principally to the coliform group. The influence of culture medium, temperature, pH, NaCl concentration and atmosphere on production of these substances was evaluated. Both of these bacteriocins could be produced in different growth media, under a pH range from 6 to 7.5, NaCl concentrations from 0.5 to 2.5% and either aerobiotic or anaerobiotic conditions. Production of klebicin K and raoultellin L occurred at 25°C and 37°C, but ceased at 42°C. However, the growth of producer strains was not reduced, thus indicating that there is no obvious correlation between numbers of culture cells and bacteriocin production. Our results show that klebicin K and raoultellin L production are stable in relation to the most common environmental factors tested. This characteristic is important in evaluating the biopreservative potential of these bacteriocins and constitutes the first step to their purification.